Post- Impact Fatigue Damage Analysis of Quasi Isotropic - Raghu V. Prakash; Mathew John (Fracture and Structural Integrity)
Carbon fiber reinforced plastic (CFRP), widely used in aircraft structures is susceptible to accidental low velocity impacts during manufacture or while in service. The damage due to impact, though small initially, can progress due to fatigue loading to cause final fracture. In this study, the CFRP laminates subjected to three different energy levels of low velocity impact were tested under constant amplitude and aircraft fatigue spectrum loading conditions till it reached the failure state. The infrared thermography NDT technique was used to understand the damage distribution across the specimen after fatigue loading of impacted specimens. The cooling response curve of specimens was obtained by the active thermography technique for different experimental conditions, namely, heat transfer by the transmission or reflection mode and impacted or un-impacted surface facing camera. The cooling response obtained when the impact damage as well as heating was on the rear surface provided a good correlation with the damage volume quantified through X-ray CT image processing. The temperature rise observed by passive thermography technique at the fiber/ply breakage during static residual strength tests was found to be proportional to the load drop and extent of pre-existing damage.